2019
DOI: 10.3389/fpsyg.2019.01641
|View full text |Cite
|
Sign up to set email alerts
|

Alpine Ski Coaches’ and Athletes’ Perceptions of Factors Influencing Adaptation to Stress in the Classroom and on the Slopes

Abstract: Research examining the student-athlete experience proposes a number of factors that can be both sources of stress and/or support. The dual career pathway offers a number of potential positive outcomes including psychological, social, and financial benefits; however, challenges including time management, fatigue, and restricted social activities are well documented. In consideration of the multidimensional student-athlete experience and the numerous factors that influence the complexity of potential stress, a m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 68 publications
1
19
0
1
Order By: Relevance
“…According to this model, the process of gaining insight and cognitively assimilating emotional events into existing schemas decreases demands on working memory and reduces uncertainty regarding the stressful situation (Klein and Boals, 2001;Graybeal et al, 2002;Schwartz and Drotar, 2004). Making sense of COVID-19 measures (e.g., quarantine, canceled sporting events) is important for athletes' positive stress adaptation and emotional well-being (Davis et al, 2019). Undertaking WED may encourage athletes to consider the implications of restrictions on sport participation in relation to wider global priorities (e.g., mortality rates) and promote their perspective taking, empathy, and mental health (Botterill and Brown, 2002;Meyer and Fletcher, 2007).…”
Section: Cognitive Adaptationmentioning
confidence: 99%
“…According to this model, the process of gaining insight and cognitively assimilating emotional events into existing schemas decreases demands on working memory and reduces uncertainty regarding the stressful situation (Klein and Boals, 2001;Graybeal et al, 2002;Schwartz and Drotar, 2004). Making sense of COVID-19 measures (e.g., quarantine, canceled sporting events) is important for athletes' positive stress adaptation and emotional well-being (Davis et al, 2019). Undertaking WED may encourage athletes to consider the implications of restrictions on sport participation in relation to wider global priorities (e.g., mortality rates) and promote their perspective taking, empathy, and mental health (Botterill and Brown, 2002;Meyer and Fletcher, 2007).…”
Section: Cognitive Adaptationmentioning
confidence: 99%
“…The internal consistency presented by Main and Grove [ 29 ] showed values of α ranging from 0.72–0.86, and the six-factor solution accounted for 67.01% of the common item variance. The following Cronbach’s α has been reported from a study on alpine skiers: depressed = 0.84, vigor = 0.76, physical symptoms = 0.50, sleep disturbances = 0.87, stress = 0.81, and fatigue = 0.80 [ 35 ]. Another study reported the overall internal consistency as α = 0.90 [ 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…An ASRM that has been considered to be promising in monitoring athletes [ 28 ] is the Multicomponent Training Distress Scale (MTDS) [ 29 ]. The instrument has been used in different sports, including swimming [ 30 ], rowing [ 31 ], soccer [ 32 , 33 ], cycling [ 34 ], alpine skiing [ 35 ], and tennis [ 36 ]. The instrument combines measures of mood disturbances, perceived stress, and symptoms of acute overtraining over a small number of items (22 questions) [ 29 ], and provides an insight into the intensity and frequency of psycho-behavioral responses [ 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Fundamentally, collegiate athletes have two major roles they must balance as part of their commitment to a university: being a college student and an athlete. Academic performance is a significant source of stress for most college students (Aquilina, 2013 ; López de Subijana et al, 2015 ; de Brandt et al, 2018 ; Davis et al, 2019 ). This stress may be further compounded among collegiate athletes based on their need to be successful in the classroom, while simultaneously excelling in their respective sport (Aquilina, 2013 ; López de Subijana et al, 2015 ; Huml et al, 2016 ; Hamlin et al, 2019 ).…”
Section: Academic Stressmentioning
confidence: 99%
“…Academic performance, social demands, adjusting to life away from home, and financial challenges are just a few of the burdens college students must confront (Humphrey et al, 2000 ; Paule and Gilson, 2010 ; Aquilina, 2013 ). In addition to these stressors, collegiate athletes are required to spend a substantial amount of time participating in activities related to their sport, such as attending practices and training sessions, team meetings, travel, and competitions (Humphrey et al, 2000 ; López de Subijana et al, 2015 ; Davis et al, 2019 ; Hyatt and Kavazis, 2019 ). These commitments, in addition to the normal stress associated with college life, may increase a collegiate-athlete's risk of experiencing both physical and mental issues (Li et al, 2017 ; Moreland et al, 2018 ) that may affect their overall health and wellness.…”
Section: Introductionmentioning
confidence: 99%